[Au(9‐methylcaffein‐8‐ylidene)2]+/DNA Tel23 System: Solution, Computational, and Biological Studies. Issue 55 (6th September 2017) - Papi, Francesco; Bazzicalupi, Carla; Ferraroni, Marta; Massai, Lara; Bertrand, Benoît; Gratteri, Paola; Colangelo, Donato; Messori, Luigi
Abstract: Physicochemical methods have been used to investigate interactions occurring in solution between the dicarbene gold(I) complex [Au(9‐methylcaffein‐8‐ylidene)2 ]BF4 (AuNHC) and a human telomeric DNA sequence, namely Tel23. Circular dichroism measurements allow identification of the conformational changes experienced by Tel23 upon interaction with AuNHC, and the respective binding stoichiometries and constants were determined. Computational studies provide a good link between previous crystallographic results of the same system and the present solution data, offering an exhaustive description of the inherent noncovalent metallodrug–DNA interactions. Remarkably, we found that a preformed AuNHC/Tel23 adduct is capable of producing strong and selective inhibition of the enzyme telomerase. The latter feature is mechanistically relevant and might account for the conspicuous in vitro anticancer properties of the investigated dicarbene gold(I) complex. Abstract : Refold then interfere : Solution studies, based on CD measurements and confirmed by computational studies, showed that the formation of the AuNHC/Tel23 adduct is accompanied by a general conformational rearrangement of the Tel23 sequence (see figure). Moreover, binding stoichiometries and constants were determined. Biological studies showed the ability of the preformed adduct to interfere with telomerase activity in cancer cells.